Fixing another firm's mistake: how should recovering firms react?. Issue 1 (1st October 2019) - Bahmani, Navid; Jin, Zhenyu; Ghose, Sanjoy
Abstract : Purpose: While within-firm service failure and recovery have been studied extensively, the context in which a service failure at one firm "spills over" and provides an opportunity for an external firm (a subsequent service provider) to recover (compensate) a customer has received limited attention. This study aims to examine how the extent of a service failure plays a role in how external firms should shape their recovery efforts, and how customers' evaluations of the recovering firm and their feelings of unhappiness are affected. Design/methodology/approach: A pretest conducted on MTurk gauged participants' perceptions of equitability of the external firm's recovery effort. In the main study, a 3 × 3 between-subjects experiment examined the effects of failure extent and external recovery type on evaluations of the recovering firm and reduced feelings of unhappiness. Findings: It is found that equity judgments remain consistent in the external recovery context; transferred negative affect is able to be mitigate only in low-failure scenarios, and customers' evaluations of the external firm increase only in high-failure scenarios. Research limitations/implications: The use of hypothetical scenarios, as opposed to the employment of a field study, is the primary limitation of the study. Originality/value: This research finds that external firms can reap the benefits of another firm's service failure by offering no-cost recoveries, rather than ones that carry some form of cost.